Mitochondrial defects in sporadic inclusion body myositis—causes and consequences - Iu, Elsie Chit Yu; So, Ho; Chan, Chi Bun (Frontiers in Cell and Developmental Biology, 2024)
Myopathies (IIM), characterized by unique pathological features such as muscle inflammation, rimmed vacuoles, and protein aggregation within the myofibers. Although hyperactivation of the immune system is widely believed as the primary cause of IIM, it is debated whether non-immune tissue dysfunction might contribute to the disease's onset as patients with sIBM are refractory to conventional immunosuppressant treatment. Moreover, the findings that mitochondrial dysfunction can elicit non-apoptotic programmed cell death and the subsequent immune response further support this hypothesis. Notably, abnormal mitochondrial structure and activities are more prominent in the muscle of sIBM than in other types of IIM, suggesting the presence of defective mitochondria might represent an overlooked contributor to the disease onset. The large-scale mitochondrial DNA deletion, aberrant protein aggregation, and slowed organelle turnover have provided mechanistic insights into the genesis of impaired mitochondria in sIBM. This article reviews the disease hallmarks of sIBM, the plausible contributors of mitochondrial damage in the sIBM muscle, and the immunological responses associated with mitochondrial perturbations. Additionally, the potential application of mitochondrialtargeted chemicals as a new treatment strategy to sIBM is explored and discussed.